Influence of probiotic preparations on metabolic processes, enterobiasis and the level of endogenous intoxication of animals - Osepchuk Denis; Semenenko Marina; Kuzminova Elena; Semenenko Ksenia (E3S Web of Conferences, 2022)
The article presents the results of studies of the probiotic preparations influence, including bacteria of various strains, on the microflora, biochemical blood homeostasis, the level of endogenous intoxication of young pigs, as well as on their productivity and safety. It was determined that feeding a polyassociative probiotic preparation containing a consortium of strains of lactic acid and propionic acid bacteria (Biovet-2), as well as the microbial mass of living bacteria B. subtilis and B. licheniformis (Subtilis), had a positive effect on the formation of microbiocenosis in the intestines of piglets, contributing to a stable clinical result, characterized by an increase in the content of lactobacilli in the intestinal chyme. Their introduction into feed increased the body weight gain of animals by 20.9% and 19.2% with 100% safety of animals. The use of probiotics contributed to the intensification of metabolic processes in the body of young pigs, in particular, an increase in serum of total protein by 7.1% and 10.6%, an increase of glucose by 12.8% and 10.9%, as well as a decrease in the level of endogenous intoxication. Thus, the inclusion of probiotic preparations in the technology of young pigs rearing can become an effective way to prevent gastrointestinal diseases based on environmentally friendly mechanisms for maintaining a high level of intestinal colonization resistance.